MULTIFUNCTIONAL MODELING OF REGIONAL SOLID WASTE MANAGEMENT SYSTEM TAKING INTO ACCOUNT SYNERGISTIC EFFECT - Писаренко, П. В.; Самойлік, М. С. (Scientific Progress & Innovations, 2017)
The article formulates the balance scheme of the solid waste of life cycle in the region, which allowed the ecological and economic model development of waste management optimal control and to determine the scope of the management scenarios optimization at the theoretically optimal values ​​of the parameters. Based on the model management area solid waste management offered algorithm for determining the optimal management strategies and mechanisms for their implementation, which allows you to solve the problem of optimizing the development of waste circulation of the sphere for a given set of variables and system state parameters for a particular type of the life cycle sphere. The developed model has a set of feasible solutions and, therefore, offers a selection of the best of them, taking into account the objective functions. Reasonably practical application of this model on the example of Poltava region based on the optimization of three objective functions: environmental risks for public health from the scope of solid waste management; maximization profits with minimum investment in this sphere; power consumption of the waste management system.